Limbah Cangkang Telur Ayam Ras (Gallus Domesticus) Sebagai Bahan Pupuk Untuk Memperbaiki Sifat Kimia Tanah - Irna Il Sanuriza; Dwi Kartika Risfianty (Universitas Pendidikan Mandalika Mataram, 2020)
Degradation of soil quality caused by the use of chemical fertilizers is a serious problem in agriculture. The use of environmentally friendly fertilizers is an important step to increase soil quality. One of them is by utilizing chicken eggshell waste as organic fertilizer. This study aims to utilize chicken eggshells with the right dose to improve soil quality. This research is a quantitative study using a completely randomized design. The results showed that the eggshell waste had the potential as an organic fertilizer to improve soil chemistry. Application of 6.25 gram egg shell/planting-hole can increase soil pH, C-Organic and N-total levels.